Experimental study on dynamic response of model shield tunnel induced by moving-axle loads of subway train - Mengxi Zhang; Xiaoqing Zhang; Lei Li; Chengyu Hong (International Journal of Distributed Sensor Networks)
A new testing method was introduced to apply moving-axle loads of a subway train on a track structure. In order to investigate the dynamic responses of the shield tunnel subjected to moving-axle loads, a series of laboratory model tests were conducted in a 1/40 scale model tunnel. The influences of the axle load, the wheel speed, and the cover depth of the shield tunnel on the vertical displacement and acceleration of the lining were presented and discussed. Parametric studies revealed that the vertical displacement–time history of the lining presents a “W” shape due to the combined action of two axles of a bogie. The peak value of the vertical displacement increased with the axle load linearly, while it decreased with the increase in the cover depth. Moreover, response time of the displacement decreased with the increase in the wheel speed, but the peak values remained stable at the same level. Finally, a three-dimensional dynamic finite element model was adopted to simulate the movement of the axle loads and calculate the responses of the lining. The numerical results analysis agrees well with experimental results.